2015
DOI: 10.1002/xrs.2638
|View full text |Cite
|
Sign up to set email alerts
|

Radiostability of cefoselis sulfate in the solid state

Abstract: aThe possibility of applying radiation sterilization to cefoselis sulfate was investigated. The lack of changes in the chemical structure of cefoselis sulfate irradiated with a dose of 25 kGy, required to attain sterility, was confirmed by ultraviolet, Fourier transform infrared, Raman, differential scanning calorimetry, scanning electron microscopy, X-ray diffraction and chromatographic methods. Electron paramagnetic resonance studies showed that radiation has created some radical defects that concentration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Previous research concerning the radiostability of β-lactams antibiotics have confirmed their susceptibility to degradation [7,8,9,10,11,12,13]. Test results—both identification methods and stability tests—carried out for solid ERP reflect this statement.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Previous research concerning the radiostability of β-lactams antibiotics have confirmed their susceptibility to degradation [7,8,9,10,11,12,13]. Test results—both identification methods and stability tests—carried out for solid ERP reflect this statement.…”
Section: Discussionmentioning
confidence: 62%
“…For this reason, it is particularly important to choose the suitable sterilization method for ERP and irradiation seems to be the most advantageous approach. However, the use of this method requires detailed studies and confirmation of the impact of irradiation on the pharmaceutical properties and structure of the drug [7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research concerning the radiostability of β-lactams antibiotics has confirmed their susceptibility to degradation (12)(13)(14)(15)(16)(17).…”
Section: Resultsmentioning
confidence: 85%
“…The spectrum of the non-irradiated sample does not differ from the background of the spectrometer, thus the concentration of radicals is less than 0.1 ppm. Unlike many irradiated drugs (7,8,10) EPR spectrum of irradiated BP sample (radiation dose 25 kGy) is very stable at room temperature, and the concentration of free radicals 14.1 ± 0.3 ppm is constant vs. time after irradiation as shown in Figure 5. Although we can not exclude that irradiation also causes other radiological defects (breaking the C-C bonds), we have shown that the radiation dose of 25 kGy does not create much radical-type damage.…”
Section: Resultsmentioning
confidence: 98%
“…In clinical treatment a combination of these compounds is used in a 1 : 1 weigh ratio as a powder to prepare intravenous solution and according to the European Pharmacopoeia 9 th this composition have to meet all requirements for preparations administered parenterally and containing an antibiotic component (6). One of the most advantageous methods for maintenance of sterility for this combination is irradiation, as demonstrated by radiolytic studies of other β-lactam antibiotics (7)(8)(9)(10)(11)(12)(13). Therefore, it is extremely important to verify the stability and potential changes in physicochemical properties of the component which is an adjunct agent to antibacterial therapy and during production must be subjected to the same processes.…”
mentioning
confidence: 99%